Análise bibliométrica sobre acidentes nucleares: um estudo na base de dados da Web of Science - NASCIMENTO, Marciel de Sousa (2022)
This work shows the importance of bibliometrics for the analysis of scientific publications on nuclear accidents, besides being a theme still little explored in the scientific environment, but it is of great relevance, because of this we tried to emphasize the main countries that publish more about the It also indicates what led the authors to publish about nuclear accidents, which types of nuclear accidents are most interested in the publications. Also highlighting which are the areas of greatest importance in research on nuclear accidents, the most cited records, the journals with the greatest impact factor, the authors and the institutions that are reported on this subject in the scientific world, are future studies in the field. of information sciences when dealing with the topic of nuclear accident, facilitate research on future work on the above-mentioned theme. This research carried out a bibliometric analysis in the Web of Science (WoS) database, considered one of the oldest and largest databases of scientific works in the world, and scientific articles from the last 53 years (1965 to 2018) were selected, if works related to the search term “nuclear accident”, keyword in English that was used in the selection base of the scientific works. Through completed surveys, Japan and the United States were the leading countries in the ranking of nuclear accident publications with 30% and 15% of total publications respectively, further realizing that the Japanese institutions were the most productive in registration issues. On the subject researched, moreover, the most studied accident was what happened at the nuclear power plant of Fukushima, Japanese city, also affected most of the authors responsible for the records published in the WoS database are of Japanese origin, note also One of the areas of major concern of the authors is related to environmental and safety issues. Finally, it was possible to realize that countries where major nuclear accidents occurred were the ones that invested the most in research related to the mentioned theme, taking protective measures, so that such accidents do not occur again damages caused by environmental and socio-environmental damages without precedents.